Significance, Effectiveness and Prospects of Development of Enzyme Preparations in Modern Pharmaceutical Practice - U.M. Tillaeva1, D.T. Gaibnazarova2, F.S. Jalilov3, B.Sh. Abdullaev4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This article presents topical issues devoted to the study and prospects for the development of enzymepreparations in modern pharmaceutical practice in the Republic of Uzbekistan. In the context of existingresources, the rational use of high-quality, effective, safe medicines and the creation of new ones bycombining local raw materials with an innovative approach is a priority. The expediency of combinations ofdrugs useful for medical practice for effort or combination of effects is noted.In medicine, nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to treat rheumatoidarthritis and other inflammatory diseases. NSAIDs are the basic drugs in the pharmacotherapy of manychronic, acute diseases, normalizing biochemical parameters and the functional state of blood cells. Thesedrugs are taken over-the-counter and for a long time, and therefore resolving issues, related to the safety oftheir use, the search for a combination is relevant. Currently, domestic developments of NSAIDs (fensulkal,blizketazin) are being carried out by combining enzymes (to enhance the effect) and in justified rectal andtransfermal medicinal forms. Many diseases are associated with impaired secondary enzyme deficiency.Clinical studies confirm the high effectiveness of the combination of NSAIDs with enzyme preparations. Theclassification of proteolytic enzymes, the importance, scale and resources of the prevalence of plant enzymesin the Republic are presented. Of particular interest is the papaya (melon tree). Papain and chymopapain arelatex enzymes of the fruits of the melon tree.